Electroclinical characteristics of MRI negative focal epilepsy: A video-EEG study - Ristić Aleksandar J.; Arsić Aleksandra; Trajković Goran; Berisavac Ivana; Kisić Bojana (Vojnosanitetski Pregled)
Background/Aim. Epileptogenic lesions carry intrinsic epileptogenicity or epileptogenic potential in their close vicinity. One third of patients with focal epilepsy have no epileptogenic lesions magnetic resonance imaging [MRI(-)]. The aim of this study was to determine the epileptogenic zone investigating electrical and clinical properties of MRI- patients. Methods. In 180 patients with focal epilepsy we analyzed 1,712 seizures for interictal and ictal electroencephalography (EEG) and seizure semiology. If multiple seizures occurred we took the best seen on video as an example, with secondary generalized tonic-clonic seizures (GTCS) if it occurred. Brain MRI was focused to investigate the zone of ictal EEG onset. Electroclinical properties of the MRIpatients were compared to lesion positive patients [MRI(+)]. Results. A single epileptogenic lesion was identified in 68.89% [hippocampal sclerosis (HS) in 58, focal cortical dysplasia (FCD) in 28 and other pathologies in 38 patients]. MRI(-) patients had significantly less interictal epileptiform abnormalities, and presented more often (p < 0.001) with secondary GTCS as the only seizure. Eye opening, hypermotor seizure, bilateral asymmetric clonic seizure, vocalization, and contralateral body turning occurred more frequently in the MRI- group compared to the MRI+ one. MRI- patients share some semiological features with FCD as opposed to HS patients. Conclusion. MRIepilepsy patients frequently present with electroclinical features seen in frontal lobe epilepsy or in epilepsy associated with FCD.